2021
DOI: 10.1093/eurjcn/zvab123
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of preoperative education interventions on improving perioperative outcomes of adult patients undergoing cardiac surgery: a systematic review and meta-analysis

Abstract: Background Cardiac surgeries pose as an emotional experience for patients. Preoperative education is known to positively alter people’s perceptions, emotions, and mitigate surgical distress. However, this intervention’s effectiveness in improving perioperative outcomes among patients undergoing cardiac surgery lacked rigorous statistical synthesis and remains inconclusive. Aims The aim was to synthesize the effectiveness of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…Ng et al (2021) found that preoperative education had large significant effects on reducing post intervention preoperative anxiety, length of ICU stay, and improving knowledge in adult patients undergoing cardiac surgery. Small significant effects were also found for reducing postoperative anxiety, depression, and enhancing satisfaction.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Ng et al (2021) found that preoperative education had large significant effects on reducing post intervention preoperative anxiety, length of ICU stay, and improving knowledge in adult patients undergoing cardiac surgery. Small significant effects were also found for reducing postoperative anxiety, depression, and enhancing satisfaction.…”
Section: Resultsmentioning
confidence: 98%
“…Three systematic reviews (Burgess et al, 2019, Ng et al, 2021, Van der Gucht et al, 2021) provided evidence on the effectiveness of preoperative educational interventions on improving outcomes of patients awaiting elective surgery. One of the reviews targeted patients awaiting orthopaedic surgery (spinal surgery), another on cardiac surgery, and the third review did not have any specific surgical focus (elective surgery).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When hospitalization and surgery are combined, patients' concerns and anxieties increase (Chen, Soens, & Kovacheva, 2022;Ng, Wang, Shen, Toh, & He, 2021) Surgery is stressful and may have an adverse effect on a person's physical and mental health (Vaughn, Wichowski, & Bosworth, 2007;Yang et al, 2022). Emergency surgery candidates frequently display tension and anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…Emergency hospitalization is associated with fear and anxiety, but invasive and surgical interventions increase this anxiety and fear (Chen et al, 2022;Ng et al, 2021) . As a result, patients undergoing emergency surgery were chosen for this study.…”
Section: Introductionmentioning
confidence: 99%